An infection-microenvironment-targeted and responsive peptide-drug nanosystem for sepsis emergency by suppressing infection and inflammation - He, Wei; Fu, Daan; Gai, Yongkang; Liu, Xingxin; Yang, Chang; Ye, Zhilan; Chen, Xu; Liu, Jia; Chang, Bingcheng (Asian journal of pharmceutical sciences, 2023)
Sepsis is a life-threatening emergency that causes millions of deaths every year due to severe infection and inflammation. Nevertheless, current therapeutic regimens are inadequate to promptly address the vast diversity of potential pathogens. Omiganan, an antimicrobial peptide, has shown promise for neutralizing endotoxins and eliminating diverse pathogens. However, its clinical application is hindered by safety and stability concerns. Herein, we present a nanoscale drug delivery system (Omi-hyd-Dex@HA NPs) that selectively targets infectious microenvironments (IMEs) and responds to specific stimuli for efficient intervention in sepsis. The system consists of omiganan-dexamethasone conjugates linked by hydrazone bonds which self-assemble into nanoparticles coated with a hyaluronic acid (HA). The HA coating not only facilitates IMEs-targeting through interaction with intercellular-adhesion-molecule-1 on inflamed endotheliocytes, but also improves the biosafety of the nanosystem and enhances drug accumulation in primary infection sites triggered by hyaluronidase. The nanoparticles release dual drugs in IMEs through pH-sensitive cleavage of hydrazone bonds to eradicate pathogens and suppress inflammation. In multiple tissue infection and sepsis animal models, Omi-hyd-Dex@HA NPs exhibited rapid source control and comprehensive inflammation reduction, thereby preventing subsequent fatal complications and significantly improving survival outcomes. The bio-responsive and self-delivering nanosystem offers a promising strategy for systemic sepsis treatment in emergencies.